Criminal recidivism rates globally: a 6-year systematic review update - Yukhnenko, D; Farouki, L; Fazel, S (Elsevier, 2023)
Objectives: Previous work has shown that direct comparison of recidivism rates between jurisdictions without accounting for potential sources of their variation can be misleading. We aimed to systemically review data on recidivism rate internationally and explore sources of between-country variation.